Electro-fused magnesia, method for its production and use thereof
Patent Information
- Application Number
- CN202611479348.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-11-03
AI Technical Summary
Existing fused magnesia has poor thermal shock resistance and is prone to thermal stress concentration in environments with frequent temperature fluctuations, leading to crack initiation and propagation.
In the preparation of fused magnesia, 1-3% of graphite powder is added as an auxiliary material. Graphite powder has the functions of pore formation, reduction and impurity removal and residual carbon toughening at high temperatures. Through the synergistic effect of suspended lightly calcined magnesia powder and graphite powder, the internal pore structure of fused magnesia is optimized to form micropores with a specific ratio and distribution, thereby enhancing the thermal shock resistance and fracture toughness of the material.
It significantly improves the thermal shock resistance and fracture toughness of fused magnesia, increases the micropore area ratio by 78%~261%, increases the number of water-cooled thermal shock cycles at 1100℃ by 50%~125%, increases fracture toughness by 17%~39%, increases MgO purity to 97.7%~98.3%, and maintains a high bulk density of ≥3.46 g/cm3.
Smart Images

Figure CN123026431A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory materials technology, and in particular to an electrofused magnesia, its preparation method, and its application. Background Technology
[0002] Fused magnesia is a high-purity magnesia refractory material made from high-purity light-burned magnesia powder (or magnesite) melted in an electric arc furnace at approximately 3000℃ and then slowly cooled and crystallized. It has a high melting point of 2852℃, excellent thermal stability, and outstanding resistance to alkaline slag erosion, making it an indispensable basic raw material for high-temperature industries. Large-crystal fused magnesia, due to its large crystal size, low porosity, high bulk density, and high MgO content, is widely used in core steelmaking processes such as converter steelmaking, electric arc furnace steelmaking, and ladle refining, as well as in cutting-edge fields such as nuclear reactors and high-temperature coatings for aero-engines. China is the world's largest producer of fused magnesia, but structural problems such as high energy consumption, high pollution, and a product structure biased towards low- and mid-range products have long existed, resulting in a relatively weak supply capacity of large-crystal high-grade fused magnesia.
[0003] Magnesia, as a refractory material, has a fatal weakness: poor thermal shock resistance. The coefficient of thermal expansion of periclase (MgO) crystals is as high as (14~15)×10⁻⁶. -6 In environments with frequent temperature fluctuations, fused magnesia is prone to thermal stress concentration, leading to crack initiation and propagation, ultimately causing refractory material spalling and damage. Therefore, improving the thermal shock resistance of fused magnesia has always been an important technical challenge in this field. Summary of the Invention
[0004] This invention provides an fused magnesia, its preparation method, and its application, in order to solve the problem of poor thermal shock resistance in existing fused magnesia.
[0005] According to a first aspect of the present invention, the present invention provides fused magnesia, the raw materials for which are prepared include suspended light-burned magnesia powder and graphite powder, wherein the amount of graphite powder added is 1 to 3% of the mass of the suspended light-burned magnesia powder.
[0006] The fused magnesia provided by this invention uses suspended light-burned magnesia powder as a base material and adds a specific proportion (1~3%) of graphite powder. It utilizes the triple functions of graphite powder at the high temperature of electrofusion—pore-forming, reduction and impurity removal, and residual carbon toughening—to create a synergistic effect with the highly active suspended light-burned magnesia powder. This specific ratio range maintains a high bulk density (≥3.46 g / cm³). 3 Under the premise of optimizing the internal pore structure of fused magnesia, the thermal shock resistance and fracture toughness of fused magnesia were significantly improved.
[0007] When the graphite powder content is less than 1%, the pore-forming and impurity-removing effects are not significant. When the graphite powder content is higher than 3%, excessive gas generation leads to excessively high porosity, some pores become interconnected forming open pores, and the bulk density decreases to 3.46 g / cm³. 3 The following does not meet the requirements of industry standard YB / T 5266-2023 for large-crystal fused magnesia. This invention, through extensive experimentation, determined an optimized addition range of 1% to 3%. Within this range, the micropore area ratio is 3% to 7%, the apparent porosity is ≤3%, and the bulk density is ≥3.46 g / cm³. 3 This achieves a balance between microporous toughening and maintaining bulk density.
[0008] According to the fused magnesia of the present invention, the suspended light-burned magnesia powder is obtained by suspension roasting of magnesite flotation concentrate powder as raw material, and its particle size is 200-300 mesh; the bulk density of the suspended light-burned magnesia powder is <1 t / m³. 3 (Preferred value: 0.3t / m) 3 ~0.8t / m 3 ), MgO content ≥96% (preferably 96%~99%).
[0009] In this invention, the suspended light-burned powder has a fine particle size, high activity, and large specific surface area, which is beneficial for the uniform dispersion and full contact of graphite powder, ensuring that the graphite powder is evenly distributed in the melt; the suspended light-burned powder itself has high porosity and low bulk density (<1 t / m³). 3 The process involves entraining more air into the melt, creating a superimposed pore-forming effect with the gas generated by graphite oxidation. The rapid melting characteristics of the suspended light-burned powder allow some graphite powder to be encapsulated by the melt before complete oxidation, creating conditions for residual carbon retention. This is a technical effect that cannot be achieved using ordinary light-burned powder or magnesite lumps.
[0010] According to the fused magnesia of the present invention, the particle size of the graphite powder is 180~325 mesh; the fixed carbon content of the graphite powder is ≥95% (preferably 95%~99%).
[0011] In this invention, graphite powder functions as a pore-forming agent, a reducing agent for impurities, and a toughening agent. In an electric arc furnace melt at 2800-3000℃, the graphite powder reacts with residual oxygen in the melt and its own interlayer oxygen-containing functional groups to generate CO2 / CO gas. Simultaneously, the graphite particles oxidize and burn off at high temperatures, leaving pores. These gases and pores are sealed inside the grains during the rapid crystallization of periclase, forming micron-sized closed pores. At the high temperature of the electric arc furnace, the graphite powder reacts with other impurity oxides, such as SiO2, undergoing a carbothermic reduction reaction (SiO2 + C → SiO↑ + CO↑), removing impurities in gaseous form and improving the purity of MgO. Simultaneously, the gas generated by this reaction further contributes to micropore formation, achieving a functional connection between the impurity-removing gas and the pore-forming gas. Under the condition of rapid melting of suspended lightly calcined powder and encapsulation of graphite powder, some graphite powder is not completely oxidized, remaining as nano / micron-sized carbon particles at the periclase grain boundaries. These residual carbon particles further enhance the fracture toughness of the material through crack deflection and bridging mechanisms.
[0012] According to the fused magnesia of the present invention, the pore size of the micropores in the fused magnesia is 20~70μm, the micropore area accounts for 3~7%, and the apparent porosity is ≤3% (preferably 1.5%~2.5%).
[0013] The fused magnesia provided by this invention forms micropores with specific pore sizes and area ratios internally, and has an extremely low apparent porosity. These dispersed micron-sized closed pores are beneficial for improving the material's toughness. They can effectively prevent crack propagation or cause cracks to deflect and branch during propagation, thereby absorbing energy and significantly improving the material's thermal shock resistance. At the same time, the extremely low apparent porosity ensures that most of these micropores are closed pores, having little impact on the material's bulk density and strength.
[0014] According to the fused magnesia of the present invention, the bulk density of the fused magnesia is ≥3.46 g / cm³. 3 (Preferred value: 3.46 g / cm³) 3 ~3.52g / cm 3 The MgO content is 94%~99%, and the periclase crystal size is 0.7~1.5mm.
[0015] The above performance indicators demonstrate that while significantly improving the thermal shock resistance, the fused magnesia of the present invention has not sacrificed other key performance indicators that fused magnesia must possess as a high-end refractory raw material, ensuring that the product meets or even exceeds industry standards.
[0016] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned fused magnesia, comprising the following steps: mixing suspended lightly calcined magnesia powder and graphite powder in a mass ratio to obtain a mixture; smelting the mixture at 2800~3000℃; and cooling and crystallizing after smelting.
[0017] The method for preparing fused magnesia provided by this invention transforms specific raw materials into a product with specific properties through a series of steps: mixing, high-temperature melting, and cooling crystallization. The high-temperature melting at 2800~3000℃ provides the energy necessary for the complete melting of magnesium oxide and for a series of physicochemical reactions, such as carbothermic reduction and oxidation-induced gasification of graphite powder.
[0018] According to the method for preparing fused magnesia of the present invention, the smelting current is 8000~15000A, the voltage is 100~180V, and the smelting time is 3~6h.
[0019] This invention, by controlling the energy input of the electric arc furnace, can stably maintain the temperature of the molten pool within the target range, ensuring the smooth progress of the smelting process and the full completion of the chemical reaction.
[0020] According to the method for preparing fused magnesia of the present invention, the mixing method is dry mechanical stirring or airflow mixing, and the mixing time is 10~30 min.
[0021] This invention employs dry mechanical stirring or airflow mixing to ensure that graphite powder, which accounts for a small percentage by mass, can be fully and uniformly dispersed into a large amount of suspended lightly calcined magnesium oxide powder, which is beneficial for the formation of a dispersed, homogeneous microporous structure during subsequent smelting.
[0022] According to the method for preparing fused magnesia of the present invention, the cooling rate for cooling crystallization is 0.5~5℃ / min, and the cooling time is 72~168h.
[0023] The present invention employs a slow cooling rate for a long time, which is conducive to the full growth of periclase crystals, thereby obtaining large-sized crystals. At the same time, the slow cooling process also helps to encapsulate the gas in the melt inside the crystal to form stable closed pores, rather than escaping or forming through open pores.
[0024] According to a third aspect of the invention, the invention also provides the application of the above-described fused magnesia in refractory materials.
[0025] The beneficial effects of this invention are: The fused magnesia provided by this invention utilizes the triple functions of graphite—pore formation, reduction and impurity removal, and residual carbon toughening—by adding 1-3% graphite powder to suspended light-burned magnesia powder. This results in significant beneficial effects. Compared to fused magnesia without added graphite powder, the micropore area ratio of the fused magnesia provided by this invention increases from 1.8% to 3.2%-6.5%, an increase of 78%-261%, with smaller and more uniform pore size. It fundamentally solves the problem of poor thermal shock resistance in traditional fused magnesia, increasing the number of water-cooled thermal shock cycles at 1100℃ by 50%-125%; the residual carbon toughening increases the fracture toughness from 1.8 MPa·m⁻² to 2.1-2.5 MPa·m⁻², an increase of 17%-39%. Secondly, the reduction effect of graphite effectively improved the purity of the product, increasing the MgO content from 97.5% to 97.7%~98.3%. This invention significantly improved the material's toughness while maintaining the product's high bulk density (≥3.46 g / cm³). 3 This method does not sacrifice other key performance characteristics. It is simple and inexpensive, using graphite powder, a readily available industrial raw material, which is inexpensive (approximately 3000-5000 RMB / ton). The addition amount is only 1%-3%, and it can be implemented directly on existing three-phase AC electric arc furnace production lines without additional equipment investment. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0027] Figure 1 This is a schematic diagram of the SEM microstructure of fused magnesia provided in Embodiment 2 of the present invention.
[0028] Figure 2 This is a schematic diagram of the SEM microstructure of fused magnesia provided in Comparative Example 1 of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0030] The suspended lightly calcined magnesia powder used in the following examples and comparative examples has a particle size of 200-300 mesh and an MgO content of ≥96%, and is obtained by suspension calcination of magnesite flotation concentrate powder in a suspension furnace. The graphite powder has a particle size of 180-325 mesh and a fixed carbon content of ≥95%.
[0031] Example 1 This embodiment provides an electrofused magnesia, prepared from 100 kg of suspended light-burned magnesia powder and 1 kg of graphite powder. The suspended light-burned magnesia powder has a particle size of 200-300 mesh and an MgO content of 96.5%, and is obtained by suspension calcination of magnesite flotation concentrate powder in a suspension furnace; the graphite powder has a particle size of 325 mesh and a fixed carbon content of 96%.
[0032] This embodiment also provides a method for preparing the fused magnesia, including the following steps: (1) Mixing: The above suspended light-burned magnesium oxide powder and graphite powder are put into a dry mechanical mixer and mixed for 15 minutes to make the graphite powder evenly dispersed in the suspended light-burned magnesium oxide powder to obtain a mixture.
[0033] (2) Melting: The mixture is put into a 3000kVA three-phase AC electric arc furnace. After the furnace is started, the mixture is added gradually. The melting current is 10000A, the voltage is 140V, the temperature of the molten pool is maintained at about 2850℃, and the melting time is 4 hours.
[0034] (3) Cooling and crystallization: After smelting, the power supply was stopped and natural furnace cooling was adopted. The cooling rate was about 1℃ / min and the cooling time was 120 hours to obtain microporous toughened fused magnesia. The performance indicators of the obtained fused magnesia are shown in Table 1 below.
[0035] Example 2 This embodiment provides an electrofused magnesia, which is prepared from 100 kg of suspended light-burned magnesia powder and 2 kg of graphite powder. The performance indicators of the suspended light-burned magnesia powder and graphite powder are the same as those in Embodiment 1.
[0036] This embodiment also provides a method for preparing the fused magnesia, including the following steps: (1) Mixing: Put the above raw materials into an airflow mixer and mix for 20 minutes to obtain a mixture.
[0037] (2) Melting: The mixture is put into a 3000kVA three-phase AC electric arc furnace. After the furnace is started, the mixture is added gradually. The melting current is 12000A, the voltage is 150V, the temperature of the molten pool is maintained at about 2900℃, and the melting time is 4 hours.
[0038] (3) Cooling and crystallization: After the smelting is completed, the power supply is stopped, and a controlled slow cooling method is adopted for cooling. The cooling rate is 0.8℃ / min, and the cooling time is 144 hours to obtain microporous toughened fused magnesia. The performance indicators of the obtained fused magnesia are shown in Table 1 below.
[0039] Example 3 This embodiment provides an electrofused magnesia, which is prepared from 100 kg of suspended light-burned magnesia powder and 3 kg of graphite powder. The performance indicators of the suspended light-burned magnesia powder and graphite powder are the same as those in Embodiment 1.
[0040] This embodiment also provides a method for preparing the fused magnesia, including the following steps: (1) Mixing: Put the above raw materials into a dry mechanical mixer and mix for 25 minutes to obtain a mixture.
[0041] (2) Melting: The mixture is put into a 3000kVA three-phase AC electric arc furnace. After the furnace is started, the mixture is added gradually. The melting current is 14000A, the voltage is 160V, the temperature of the molten pool is maintained at about 2950℃, and the melting time is 4.5 hours.
[0042] (3) Cooling and crystallization: After smelting, the power supply was stopped, and directional crystallization was used for cooling. By controlling the heat dissipation rate of the bottom and side walls of the furnace, the crystals were made to grow radially from the outside to the inside. The cooling rate was 0.5℃ / min, and the cooling time was 168 hours, resulting in microporous toughened fused magnesia. The performance indicators of the obtained fused magnesia are shown in Table 1 below.
[0043] Example 4 This embodiment provides an electrofused magnesia, which differs from Embodiment 3 in that the graphite powder has a particle size of 180 mesh.
[0044] This embodiment also provides a method for preparing the fused magnesia, which is the same as in Embodiment 3.
[0045] Comparative Example 1 This comparative example provides an electrofused magnesia, which differs from Example 1 in that it is prepared from 100 kg of suspended lightly calcined magnesia powder without the addition of graphite powder.
[0046] This comparative example also provides a method for preparing the fused magnesia, which is the same as in Example 2 (the mixing step is omitted, and the smelting and cooling conditions are the same).
[0047] Comparative Example 2 This comparative example provides an electrofused magnesia, which differs from Example 1 in that it is prepared from 100 kg of suspended light-burned magnesia powder and 5 kg of graphite powder. The performance indicators of the suspended light-burned magnesia powder and graphite powder are the same as those in Example 1.
[0048] This comparative example also provides a method for preparing the fused magnesia, which is the same as in Example 2 (the mixing step is omitted, and the smelting and cooling conditions are the same).
[0049] Comparative Example 3 This comparative example provides an electrofused magnesia, which differs from Example 3 in that the graphite powder has a particle size of 100 mesh.
[0050] This comparative example also provides a method for preparing the fused magnesia, which is the same as in Example 3.
[0051] Comparative Example 3 shows that when the particle size of graphite powder is less than 180 mesh, the particles are coarser. The coarse graphite particles produce larger pores, some exceeding 70 μm, forming interconnected irregular pores. The high proportion of micropore area will significantly reduce the material's thermal shock resistance and fracture toughness.
[0052] Comparative Example 4 This comparative example provides an electrofused magnesia, which differs from Example 3 in that the graphite powder has a particle size of 400 mesh.
[0053] This comparative example also provides a method for preparing the fused magnesia, which is the same as in Example 3.
[0054] Comparative Example 4 shows that when the particle size of graphite powder is greater than 325 mesh, the particles are finer. Fine-particle graphite reacts very easily when heated by electric melting. The resulting gas is dispersed and can be quickly discharged. Only a very small number of micropores can be formed, and their size is small. They do not play any role in the material's thermal shock resistance and fracture toughness.
[0055] The fused magnesia from the examples and comparative examples were subjected to the following performance tests, and the test results are shown in Table 1 below: (1) Bulk density and apparent porosity: determined according to GB / T 2997-2015 "Test methods for bulk density, apparent porosity and true porosity of dense shaped refractory products".
[0056] (2) Chemical composition of MgO, SiO2, CaO, etc.: determined according to GB / T 21114-2019 "X-ray fluorescence spectrochemical analysis of refractory materials".
[0057] (3) Crystal size and micropore characteristics of periclase: The crystal structure of the cross section of magnesia was observed by scanning electron microscopy (SEM), and microscopic images were taken. Quantitative metallographic analysis was performed using ImageJ image analysis software to test the area and proportion of micropores.
[0058] (4) Thermal shock resistance: The test shall be conducted in accordance with YB / T 376.1 "Test method for thermal shock resistance of refractory materials (water quenching method)". The sample shall be kept at 1100℃ for 30 minutes and then cooled with water. The test shall be repeated until the damaged area of the sample reaches more than 50%.
[0059] (5) Fracture toughness: The single-sided notched beam method (SENB) was used. The sample size was 3mm×4mm×36mm, the span was 30mm, and the notch depth was 2mm.
[0060] Table 1
[0061] *Note: In Comparative Examples 2 and 3, some pores are connected to form an opening.
[0062] As can be seen from Table 1 above, the fused magnesia of Examples 1-3 of the present invention maintains a bulk density ≥3.46 g / cm³. 3 Under the premise of [specific conditions], the micropore area ratio, MgO content, thermal shock resistance, and fracture toughness were all significantly better than those of Comparative Example 1. When the graphite powder addition exceeded 3% (Comparative Example 2), the overall performance of the product actually decreased. The experimental data of Comparative Example 2 showed that when the graphite powder addition exceeded 3%, excessive graphite oxidation produced too much gas, resulting in excessively high porosity and a significant decrease in bulk density to 3.42 g / cm³. 3 (lower than the industry standard requirement of 3.45 g / cm³) 3 Some pores connect to form open pores, crystal growth is hindered, and thermal shock resistance and fracture toughness decrease.
[0063] Figure 1 This is a schematic diagram of the SEM microstructure of the fused magnesia in Example 2, showing the distribution of 20-50 μm micron-sized closed pores inside the periclase grains. Figure 2 This is a schematic diagram of the SEM microstructure of fused magnesia in Comparative Example 1, showing the uneven micropores formed solely by air entrainment.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A type of fused magnesia, characterized in that, The raw materials for its preparation include suspended light-burned magnesium oxide powder and graphite powder, wherein the amount of graphite powder added is 1 to 3% of the mass of the suspended light-burned magnesium oxide powder.
2. The fused magnesia according to claim 1, characterized in that, The suspended light-burned magnesia powder is obtained by suspension roasting of magnesite flotation concentrate powder as raw material, and its particle size is 200-300 mesh; the bulk density of the suspended light-burned magnesia powder is <1 t / m³. 3 MgO content ≥96%.
3. The fused magnesia according to claim 1 or 2, characterized in that, The graphite powder has a particle size of 180-325 mesh; the fixed carbon content of the graphite powder is ≥95%.
4. The fused magnesia according to any one of claims 1-3, characterized in that, In the fused magnesia, the pore size of the micropores is 20~70μm, the micropore area accounts for 3~7%, and the apparent porosity is ≤3%.
5. The fused magnesia according to any one of claims 1-4, characterized in that, The bulk density of the fused magnesia is ≥3.46 g / cm³. 3 The MgO content is 94%~99%, and the periclase crystal size is 0.7~1.5mm.
6. The method for preparing fused magnesia according to any one of claims 1-5, characterized in that, The process includes the following steps: mixing suspended lightly calcined magnesium oxide powder and graphite powder in a certain mass ratio to obtain a mixture; smelting the mixture at 2800~3000℃; and cooling and crystallizing after smelting.
7. The method for preparing fused magnesia according to claim 6, characterized in that, The melting current is 8000~15000A, the voltage is 100~180V, and the melting time is 3~6h.
8. The method for preparing fused magnesia according to claim 6, characterized in that, The mixing method is dry mechanical stirring or airflow mixing, and the mixing time is 10~30 minutes.
9. The method for preparing fused magnesia according to claim 6, characterized in that, The cooling rate for the cooling crystallization is 0.5~5℃ / min, and the cooling time is 72~168h.
10. The application of the fused magnesia according to any one of claims 1-5 in refractory materials.
